GmWRKY46, a WRKY transcription factor, negatively regulates phosphorus tolerance primarily through modifying root morphology in soybean. (February 2022) - Liu, Xiaoqian; Yang, Yuming; Wang, Ruiyang; Cui, Ruifan; Xu, Huanqing; Sun, Chongyuan; Wang, Jinshe; Zhang, Hengyou; Chen, Huatao; Zhang, Dan
Highlights: GmWRKY46 gene belonging to group III of WRKY TF family and was significantly induced by P deprivation and mainly expressed in roots. Overexpression of GmWRKY46 in soybean exhibited more sensitive phenotype to low P stress compared with the control, whereas RNA of GmWRKY46 significantly enhanced the tolerance to P deficiency by increasing the P absorption efficiency of hairy roots. Abstract: Phosphorus (P) deficiency affects soybean growth and development, resulting in significant reduction of yields. However, the regulatory mechanism of P deficiency tolerance in soybean is still largely unclear. WRKY transcription factors are a family of regulators involved in a variety of abiotic stresses in plants while rarely reported in P deficiency. Here, we demonstrated that a soybean GmWRKY46 gene, belonging to group III of WRKY TF family, was involved in the regulation of P deficiency tolerance in soybean. The expression of GmWRKY46 in low P sensitive soybean varieties was significantly higher than that in tolerant soybean varieties. It was primarily expressed in roots and strongly induced by P deprivation. GmWRKY46 was localized in the nucleus. Compared with the control expressing the empty vector, overexpression of GmWRKY46 in soybean hairy roots exhibited more sensitive phenotypes to low P stress, while the RNA interfered GmWRKY46 significantly enhanced P deficiency tolerance by increasing the proliferation, elongation and P absorption efficiency of hairy roots. Expression patterns of a number of P-responsive genes ( GmPht1;1, GmPht1;4, GmPTF1, GmACP1, GmPAP21 and GmExpansin-A7 ) were altered in both overexpression and gene silenced plants. The results provided a novel insight into how soybean responds to low P stress and new gene that may be used to improve soybean low P tolerance through gene editing approach.